Understanding English grammar : a linguistic approach - Wardhaugh, Ronald (Malden, Massachusetts : Blackwell Publishers, 2002)
Presents a linguistic introduction to the structure of English that is accessible to students who have had little or no opportunity to study the language. This book features information about the essentials of English words, sentences, and sounds within a framework derived from modern linguistic theory. Contents: Preface. Preface to the Second Edition. 1. Preliminaries. 2. Word Classes. 3. Constituents and Phrases. 4. Basic Clauses. 5. Coordination and Embedding. 6. Clausal Variation. 7. Underlying Relationships. 8. Rules and Principles. 9. Sounds and Systems. 10. Phonetic Realization. 11. Word Formation. 12. Words and Sounds. 13. Sounds in Context. 14. Further Reading. Indexed Glossary.
Keywords: ENGLISH LANGUAGE -- GRAMMAR